Prestressed CFRP-reinforced steel columns under axial and eccentric compression. (15th July 2021) - Hu, Lili; Feng, Peng
Abstract: Buckling limits the slenderness of steel columns in applications. This highly efficient technology, using prestressed (PS) carbon fiber reinforced polymer (CFRP) strips to reinforce steel columns against overall buckling, can be applied in new structures or to strengthen existing structures, and is easy to construct. The buckling behavior of PS CFRP-reinforced steel columns is studied with axial and eccentric compression tests. Axial compression tests are conducted on 8 specimens with three different slenderness values (105, 140, and 200); eccentric compression tests are conducted on PS specimens of slenderness 105 with four different eccentric ratios (0, 1, 2, and 3). The buckling capacity and failure modes are obtained. The obvious reinforcing efficiency is achieved by PS CFRP; the buckling capacity of PS specimens can be increased by 19%–150%. The whole loading procedure is analyzed in detail to further explain the mechanism of PS CFRP reinforcing. Four possible critical states are determined, whose order depends on the reinforcing conditions and influences the cause of buckling, which is either material yielding or slacking of the concave side CFRP. Finally, a simplified model of reinforcing efficiency is preliminarily built based on the test results.